Análisis energético y exergetico para la reutilización del calor residual de los gases de combustión en un sistema de refrigeración de un furgón (2021)
This work shows a mathematical model using exergy and energy balance equations for the systems: turbocharged diesel cycle and absorption cooling system. For the diesel cycle, it is important to consider the outlet temperature in the turbocharger from the exhaust gases, which will be based on the heat input from the generator of the single-effect absorption cooling system with ammonia / water working fluid (NH3 -H2O).